Is Industrialization Conducive to Long-Run Prosperity? - Raphaël Franck; Oded Galor (Center for Economic Studies and ifo Institute (CESifo), 2015)
This research explores the long-run effect of industrialization on the process of development. In contrast to conventional wisdom that views industrial development as a catalyst for economic growth, highlighting its persistent effect on economic prosperity, the study establishes that while the adoption of industrial technology was initially conducive to economic development, it has had a detrimental effect on standards of living in the long-run. Exploiting exogenous source of regional variation in the adoption of steam engines during the French industrial revolution, the research establishes that regions which industrialized earlier experienced an increase in literacy rates more swiftly and generated higher income per capita in the subsequent decades. Nevertheless, early industrialization had an adverse effect on income per capita, employment and equality by the turn of the 21st century. This adverse effect reects neither higher unionization and wage rates nor trade protection, but rather underinvestment in human capital and lower employment in skilled-intensive occupations. These findings suggest that the characteristics that permitted the onset of industrialization, rather than the adoption of industrial technology per se, have been the source of prosperity among the currently developed economies that experienced an early industrialization.
Keywords: N33; N34; O14; O33; 330; economic growth; industrialization; steam engine